Mobile and Ubiquitous Systems: Computing, Networking, and Services 8th International ICST Conference, MobiQuitous 2011, Copenhagen, Denmark, December 6-9, 2011, Revised Selected Papers - Puiatti, Alessandro; Gu, Tao (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International ICST Conference on Mobile and Ubiquitous Systems: Computing, Networking, and Services, MobiQuitous 2011, held in Copenhagen, Denmark, in December 2011. The 34 revised full papers presented were carefully reviewed and selected from numerous submissions. They cover a wide range of topics ranging from localization and tracking, search and discovery, classification and profiling, context awareness and architecture, location and activity recognition as well as a best paper session, an industry track, and poster and demo papers.